156k views
4 votes
Which of the following is the correct factored form of the given equation?

x 2 + 3x - 4 = 0

2 Answers

6 votes
It is (x+4)(x-1) because 4 times -1 is -4 and 4-1 is 3.hope this helps
Which of the following is the correct factored form of the given equation? x 2 + 3x-example-1
User Anant Gupta
by
5.3k points
4 votes

For this case we must factor the following expression:


x ^ 2 + 3x-4 = 0

We must find two numbers that when multiplied give as result -4 and when summed give as result +3. These numbers are +4 and -1:


+ 4-1 = + 3\\4 (-1) = - 4

Then, the factorization is given by:


(x + 4) (x-1) = 0

Answer:


(x + 4) (x-1) = 0

User Vineet Bhatia
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.